MARKETING RESEARCH AND WAYS OF ITS IMPLEMENTATION (World Economics and Finance Bulletin, 2024)
This article covers marketing research and how to do it. Definitions given by economists to the term marketing research were studied and the author's approach was formed . Marketing research classification, methods and stages of its implementation are offered
Keywords: marketing; marketing research; marketing research classification; marketing research methods